Corrosion Evaluation of MEA Solutions by SEM-EDS, ICP-MS and XRD. (January 2016) - Fytianos, Georgios; Ucar, Seniz; Grimstvedt, Andreas; Svendsen, Hallvard F.; Knuutila, Hanna
Abstract: The target of this work is to evaluate three analytical techniques, ICP-MS, SEM-EDS and XRD, which can be applied in corrosion monitoring of ethanolamine based post-combustion CO2 capture plants. The work is based on analyses of the solvent and 316 SS cylinders used in thermal degradation experiments. ICP-MS is used for the determination of total Fe, Cr and Ni of the solutions as an indication of corrosivity. Additionally, the cylinder surface was examined with SEM-EDS and XRD was used for the identification of corrosion products. Finally, a discussion is given on the various techniques, their limitations and advantages.